Breaking a paradigm: IL-6/STAT3 signaling suppresses metastatic prostate cancer upon ARF expression. (3rd March 2016) - Culig, Zoran; Pencik, Jan; Merkel, Olaf; Kenner, Lukas
ABSTRACT: Interleukin 6 (IL-6)/signal transducer and activator of transcription 3 (STAT3) signaling is considered to have important oncogenic functions in prostate cancer (PCa). However, a recent study highlighted the central role of IL-6/STAT3 signaling in regulation of the ARF–MDM2–p53 senescence axis. This reversal of the postulated oncogenic properties of IL-6/STAT3 signaling in PCa has important therapeutic implications.